The role of migration experience in migrants' destination choice - Eugenia Chernina (IZA Journal of Development and Migration, 2020)
In this article, we employ a panel household survey from Tajikistan to study labor migrants' location choices in Russia. We find that labor migrants from Tajikistan consider a wide variety of economic, demographic, and geographical characteristics of Russian regions when making location choices. We also find that experienced migrants are less responsive to current regional characteristics that might suggest path dependence in destination choices by experienced migrants.
Keywords: F22; J61; R23; 330; Russia; Tajikistan; international migration; labor migration; location choice